Endoscopic Management of an Iatrogenic Colonic Perforation Using Standard Hemoclips - Kumar, Sanjeev; Kumar, Saket; Kumar, Sujit; Prakash, Vijay (Journal of Digestive Endoscopy, 2018)
Iatrogenic colonic perforation is an unusual but life‑threatening complication of colonoscopy. The recent advancement in endoscopy technology has made nonoperative treatment a safe and effective option for managing such perforations. A 70‑year‑old man sustained an iatrogenic sigmoid perforation during diagnostic colonoscopy. The abdominal X‑ray showed free gas under diaphragm. He was started on conservative management and intravenous antibiotics. He underwent a second colonoscopy after 2.5‑h, perforation was identified and closed with standard hemoclips. He recovered well and was discharged from hospital 6 days later. There are only a handful of reports in the medical literature describing successful outcomes following endoscopic management. Most of the cases have been managed with over‑the‑scope clips or endoscopic sutures that are quite expensive. In the present report, an iatrogenic sigmoid perforation was managed endoscopically with standard hemoclips. The hemoclip can be an effective, yet economical method of perforation repair in selected cases.
Keywords: Endoscopic clipping; endoscopic repair; iatrogenic colonic perforation